Case Study Employee Performance: Model Recruitment, Training, Mentoring - Primadi Candra Susanto; Sarinah Sihombing; Aswanti Setyawati; Sandrina Marina; Aisyah Rachmawati; Reza Fauzi Jaya Sakti; Devi Ratnasari (Greenation Management and Business Review, 2026)
Employee performance has become a critical determinant of organizational competitiveness, particularly in international cargo companies operating in increasingly dynamic, technology-driven, and globally integrated business environments. This study aims to analyze and develop an integrated employee performance model by examining the roles of recruitment, training, and mentoring as key human resource management practices. A qualitative approach employing a literature review method was adopted to synthesize previous empirical and theoretical studies. Relevant literature was collected from reputable national and international journals indexed in Google Scholar, Garuda, and SINTA. The selected articles were analyzed using descriptive, narrative, and content analysis techniques to identify patterns, similarities, differences, and research gaps. The findings indicate that recruitment, training, and mentoring each have a positive contribution to employee performance; however, their combined implementation provides a more comprehensive mechanism for enhancing workforce effectiveness. Recruitment ensures the acquisition of competent employees, training strengthens knowledge and technical capabilities, while mentoring facilitates knowledge transfer, employee adaptation, and continuous professional development. The study also identifies a research gap, as previous studies have predominantly examined these variables independently rather than as an integrated human resource management system. The novelty of this study lies in proposing a conceptual model that integrates recruitment, training, and mentoring to explain employee performance. The findings provide theoretical contributions to human resource management literature and practical recommendations for international cargo companies in designing sustainable strategies to improve employee performance and organizational competitiveness.